Formation mechanism of AGEs in Maillard reaction model systems containing ascorbic acid. (1st June 2022) - Liu, Lichun; Liu, Lei; Xie, Jianhua; Shen, Mingyue
Highlights: Alkaline environment can promote the production of CML and CEL but inhibit Pyr. The pathway of AGEs formation in Glu + Lys + AA model system was proposed. AA is the main precursor of AGEs formation in Glu + Lys + AA model system. GO replaced FL as the main precursor of CML formation in Glu + Lys + AA model system. Abstract: The dietary advanced glycation end products (AGEs) contribute to the development of major chronic diseases. Maillard reactions are the main mechanism for AGEs formation but their formation involving ascorbic acid (AA) is far from being fully understood. This study investigated the effect of pH (6–10) and temperature (65, 100 and 120 ℃) on AGEs formation in three model systems: glucose (Glu) + lysine (Lys), AA + Lys and Glu + Lys + AA. In addition, the formation pathway of AGEs in Glu + Lys + AA model system was proposed by carbon module labeling (CAMOLA) technique. The results suggested alkaline environment can promote the production of N -carboxymethyllysine (CML) and N -carboxyethyllysine (CEL), but inhibit the production of pyrraline (Pyr). Meanwhile the high temperature favored AGEs formation. In the U- 13 C-Glu + Lys + AA model, AA produced glyoxal (GO), methylglyoxal (MGO), CML and CEL, which was significantly higher than with Glu alone. This study provides a theoretical basis for the formation mechanism of AGEs in the Maillard reaction involving AA.